Can we make sense of free harmony? - Vogelmann, Rafael Graebin (Studia Kantiana, 2023)
Despite its centrality to Kant's account of judgments of taste, the notion of free harmony is remarkably hard to grasp. The difficulty springs, I argue, from the fact that any interpretation of this notion has to account for two desiderata that conflict under the assumption that concepts restrict imagination's freedom in composing the manifold of intuition: (a) that free harmony is compatible with a determinate cognition of the beautiful object and (b) what concept the object is subsumed under is irrelevant to determine whether or not it elicits free harmony. Guyer has objected to a number of interpretations on the ground that they cannot account for (a). I argue that Guyer's own metacognitive interpretation fails because it cannot account for (b). Based on some claims in the General remark on the first section of the Analytic, I outline an interpretation of free harmony that can make (a) and (b) compatible.